Utilizing Composted Jatropha & Neem cake and Tobacco Waste to sustain Garlic yields in Indo-Gangetic plains - Balraj Singh, Shivani Chaturvedi, Ashwani Kumar (Journal of Phytology, 2009)
The effect of composted Jatropha de-oiled cake, neem de-oiled cake and tobacco waste on morphological parameters like maximum leaf length, number of leaves, fresh and dry weight of bulb and yield was studied for Garlic (Allium sativum L.). Trials were conducted on field plots under the RBD design. The parameters recorded for plants grown on soil treated with composted organic fertilizer treatments were compared to those recorded for plants grown on chemical fertilizer treated soil and control. The results showed that the application of 2 tones per hectare mixture of composted Jatropha cake and tobacco waste (in ratio 2:1) resulted in an increase of 22.88 % in fresh bulb weight, 29.52% in dried bulb weight per plant and 18.3% in average yield of bulb as compared to control. This yield enhancement was significantly higher than control and comparable to that recorded for plants grown on soil treated with chemical fertilizers. The significant increase in garlic yield on application of composted Jatropha cake and tobacco waste is due to the availability of